Production of Carbonaceous Kenaf Fiber via Hydrothermal Carbonization Process - Munirah Ezzah, Tuan Zakaria; Saidatul Shima, Jamari; Norlirabiatuladawiyah, Che Ani; Suriati, Ghazali; Tanveer, Ahmad Khan (2015)
Hydrothermal carbonization process (HTC) is a relatively simple method to convert biomass to carbonaceous material that involves reaction in a closed system. HTC is convenient, fast and environmentally friendly way to convert b io mass into higher value of carbonaceous material. A comparison on the carbon percentage produced from HTC using Kenaf fiber is performed and the optimum HTC operating condition of Kenaf fiber is aimed. The heating process is carried out using two different conditions, with and without stirring at different time period which is 2 hours, 4 hours, 6 hours, 8 hours and I 0 hours at constant temperature of 225 °C. Vario Micro CHNS Analyzer used to determine the element values in the sample shows that for sample without stirring, sample heated for 2 hour produces lowest carbon percentage which is 52.25% and sample heated for 10 hour produces the highest carbon percentage which is 60.20% similar trend was obtained for the stirring sample heated for 2 hour produces 48 .31 % and sample heated for l 0 hour produces 56.73%. The percentage of carbon increase as the longer time period of heating. Based on the results, longer time period should be conducted to determine the optimum percentage of carbon produced.